Efektivitas Pengawasan Dan Penegakkan Hukum Di Wilayah Perairan Indonesia Sebagai Negara Kepulauan Dalam Menjaga Kedaulatan Maritim - Nabilla cahya ramadhani; Buhara Firdaus; Bayu Ashari (Jurnal Kajian Hukum dan Pendidikan Kewarganegaraan, 2026)
Indonesia, as the world's largest archipelagic country, faces significant challenges in maintaining maritime sovereignty in its vast waters, encompassing 17,000 islands and an Exclusive Economic Zone (EEZ) of 5.8 million km². This study analyzes the effectiveness of maritime supervision and law enforcement based on Law No. 17 of 2008 concerning Shipping, Law No. 32 of 2009 concerning Environmental Protection, and international conventions such as UNCLOS 1982. Using a normative juridical approach with secondary data analysis, the study found that supervision remains weak due to limitations in radar technology, patrol vessels, and inter-agency coordination, making it prone to violations such as illegal fishing, smuggling, and piracy. Effectiveness only reaches 45% based on the case enforcement index. Recommendations include strengthening the integration of the Maritime Task Force, increasing the budget, and reforming regulations for national-international synchronization. This research contributes to strengthening Indonesia's maritime sovereignty to support the vision of the Global Maritime Axis.